Climate change and Brazil’s coastal zone: socio-environmental vulnerabilities and action strategies (Sustainability in Debate, 2020)
The coastal zone, where most of the Brazilian population lives, plays a central role for discussing vulnerability and adaptation strategies to climate change. Besides saltmarshes, mangroves and coral reefs, this region also presents seagrass beds, macroalgae and rhodolith beds, forming underwater forests, which are key habitats for services such as biodiversity conservation, O2 production, and absorption of part of the CO2 from the atmosphere. Science endorses that ocean warming and acidification, sea level rise, biological invasions and their interactions with pollution, overfishing, and other stressors undermine the structure and functioning of these ecosystems, thus increasing the region's socio-environmental vulnerability. Ecosystem conservation, management and potential bioremediation/restoration using science-based solutions must be prioritized in order to reduce the vulnerability of coastal communities and the ocean.